owards a new paradigm of civil liability for autonomous vehicles: proposal for a dynamic legal framework based on levels of autonomy - Alcántara Francia, Olga Alejandra (2025)
The emergence of autonomous vehicles presents unprecedented challenges for civil liability law. This article proposes a new legal paradigm: a dynamic legal framework that adapts liability attribution to the various levels of vehicular autonomy. Through doctrinal, jurisprudential, and comparative analysis of international legislation, the inadequacy of current legal frameworks to address the complexity of autonomous systems is identified. The proposed framework establishes a liability categorization based on levels of autonomy, ranging from shared human-machine responsibility at lower levels to system and manufacturer liability at higher levels. It integrates principles of “ethics by design” and proposes a tiered insurance system. The framework’s validation includes application to hypothetical cases and expert evaluation, demonstrating its feasibility and adaptability to future technological developments. This innovative approach not only addresses existing legal gaps but also provides a flexible foundation for future legislative reforms. The article concludes that this dynamic framework is essential to balance technological innovation with effective legal protection, and it lays the groundwork for coherent and adaptive regulation of autonomous vehicles.